2020
DOI: 10.1136/bmjopen-2019-034166
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of premenstrual dysphoric disorder and its correlation with academic performance among female medical and health science students at University of Gondar, Ethiopia, 2019: a cross-sectional study

Abstract: ObjectiveTo assess the magnitude of premenstrual dysphoric disorder (PMDD) and associated factors among female students of the College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia, 2019.DesignInstitution-based cross-sectional study design.SettingCollege of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia.Participants386 participants were recruited for self-administered interview using the stratified followed by simple random sampling technique.MeasurementData were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
23
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 40 publications
(38 reference statements)
7
23
1
2
Order By: Relevance
“…PMS, which is characterized by one or more physical, emotional or behavioral symptoms during the days before menstruation, was found in 94.8% of women of reproductive age (15 to 49 years). 6 In India, it was shown that 12.2% had PMDD (premenstrual dysphoric disorder) and 67% were not interested in going to school during menstruation, and 71% reported lack of concentration during study hours. Different community-based surveys showed that the point prevalence of PMDD among women across the globe ranged from 1.2% to 6.4%.…”
Section: Need Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…PMS, which is characterized by one or more physical, emotional or behavioral symptoms during the days before menstruation, was found in 94.8% of women of reproductive age (15 to 49 years). 6 In India, it was shown that 12.2% had PMDD (premenstrual dysphoric disorder) and 67% were not interested in going to school during menstruation, and 71% reported lack of concentration during study hours. Different community-based surveys showed that the point prevalence of PMDD among women across the globe ranged from 1.2% to 6.4%.…”
Section: Need Of the Studymentioning
confidence: 99%
“…A Nigerian study also stated that PMDD prevalence in the country was 36.1%.The studies conducted in other universities of Ethiopia showed that the prevalence of PMDD ranged from 13.8% to 66.9% among medical and health science students. 6 World Health Organization 2014, with statistics consistently showing that women make more frequent attempts to end their own lives than men, it is imperative that we further understand the reasons underlying suicidal behaviors in women, in order to inform future prevention and treatment. The factors that drive an individual to suicide are often complex and varied; however, there is an increasing body of evidence that menstruation may play a significant role for some women.…”
Section: Need Of the Studymentioning
confidence: 99%
“…Menstrual pain may also increase anxiety, tension, sensitivity to rejection by others, and irritability. (2) It is important to differentiate PMS f rom Premenstrual Dysphoric Disorder (PMDD), which is a more serious subtype with predominantly psychological symptoms. (3) It is estimated that 5% to 20% of women worldwide have moderate-to-severe premenstrual complaints during their reproductive life, and up to 75% of all women of reproductive age may experience PMS symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…(3) It is estimated that 5% to 20% of women worldwide have moderate-to-severe premenstrual complaints during their reproductive life, and up to 75% of all women of reproductive age may experience PMS symptoms. (2) A study with a college population in a Turkish university found the prevalence of PMS alone and with dysmenorrhea was 71.3% and 65.9%, respectively; and up to 60% mentioned moderate or severe symptoms of PSM, VIEIRA: FOOT REFLEXOLOGY ON PREMENSTRUAL SYMPTOMS conventional medical curriculum, (10) exploring an expansion of the health-disease process and promotion of human care. The popularity of alternative medicine has increased due to the growing search for holistic approaches which emphasize integrating the body, mind, and spirit, along with physical symptoms, in improving health care and well-being.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation